Tracing the Trends of General Construction and Demolition Waste Research Using LDA Modeling Combined With Topic Intensity - Zezhou Wu; Peiying Xie; Jinming Zhang; Baojian Zhan; Qiufeng He (Frontiers Media S.A., 2022)
The study of construction and demolition waste (CDW) has attracted more and more attentions with the increasing CDW pollution caused by the large-scale infrastructure construction. This study used the Latent Dirichlet Allocation (LDA) combined with topic intensity to discover hot topics and development trends in the study area of CDW. First, the LDA was used for topic modeling to extract the existing topics from textual data. Second, the topic intensity was calculated for the extracted topics and the numerical values of the topic intensity represented the popularity of the topics. In this study, 4 topics were extracted from 1,849 relevant articles through the LDA modeling and topic intensity calculation. The results showed that the topic of "CDW management" had an upward trend. Topics such as "recycled aggregate," "environmental impact," and "study of CDW on soil" all showed a downward trend. The methods of this study can dig into the topics of CDW study and help scholars to engage in this field for better understanding the prevalence and evolution trends of these topics.